Radio frequency heating as a disinfestation method against Corcyra cephalonica and its effect on properties of milled rice. (June 2018) - Yang, Cui; Zhao, Yicun; Tang, Yali; Yang, Ruijin; Yan, Wenxu; Zhao, Wei
Abstract: Radio frequency (RF) heating has the potential to be developed as an alternative non-chemical disinfestation method. In contrast to microwave (MW), RF exhibited higher penetration depth, which helps RF to be a useful technique in disinfesting packaging foods. A 3 kW, 27.12 MHz RF system was used to validate the practical of radio frequency technology for rice moth ( Corcyra cephalonica ) control in milled rice. Rice samples were placed in the polystyrene bag and moved at a speed of 0.8 m/min, and heated in the RF system with intermittent mixing. Four electrode gaps and five sample thicknesses were chosen to confirm the optimal conditions of RF treatment. The results showed that the sample thickness of 15 mm and electrode gap of 40 mm could provide the optimum heating rate for rice. Mortality of each stage (adult, larva, egg) of C. cephalonica increased with increasing heating temperature and reached 100% while RF heated 180 s (45.8 °C), 300 s (56.9 °C), and 420 s (70 °C), respectively. No C. cephalonica was determined in the samples during 45 days storage incubation period at RF treatment to 70 °C. There were no significant differences between control and RF treated samples in quality parameters (moisture, protein, fat, gelatinization, and sensory attributes). Therefore, RF treatment may provide a practical and effective method for disinfesting milled rice without affecting product quality. Highlights: RF heating could be used as an alternative non-chemical disinfestation method. 100% morality of adult rice moth was achieved while RF heated for 180 s (45.8 °C). No rice moth was determined in the rice samples treated by RF to 70 °C during 45 days storage. Quality parameters of rice has no significant change after RF treatment.